Nursing Service Innovation Trough Total Quality Management in the Digital Age: A Scoping Review - I Gede Widhi Arka; Ni Luh Putu Dina Susanti; Luh Gede Nita Sri Wahyuningsih; Ni Nyoman Nuartini (Indonesian Journal of Global Health Research, 2025)
Hospitals are expected to deliver high-quality services at reasonable and competitive prices. TQM (Total Quality Management) is believed to be able to provide innovation to improve the effectiveness and efficiency of nursing services in the digital age. TQM is a management philosophy that focuses on the quality provided. In today's global market, TQM is an initiative aimed at addressing quality challenges and meeting patient demand, ultimately enabling hospitals to improve, particularly in the field of nursing services. This literature review is a scoping review. Data sources for the literature searches included PubMed and the ScienceDirect database. Articles reviewed were those published in the last 5 years. This literature review employed the PICO model (P: Nurse innovation, I: Total quality management, C: -, O: Digital age innovation). The inclusion criteria used were: articles focused on TQM, English-language articles, articles publications from 2020 to 2025, original research, full-text articles, and open-access articles. Exclusion criteria used include: narrative review, integrative review, scoping review, systematic review, and meta-analysis. Keywords used to search for articles were: “Nurse” AND “Total quality management” AND “Innovation” AND “Digital”. The results of the initial search for articles until they were included were described in the PRISMA diagram. The results of searching articles from PubMed obtained 12 articles, and from Science Direct 343 articles. TQM creates a culture where nurses are encouraged to identify problems, find solutions, and generate innovative ideas for nursing services in the digital age.